2019
DOI: 10.4253/wjge.v11.i11.523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the risk of adverse events with interventional endoscopic retrograde cholangiopancreatography and endoscopic ultrasound procedures in cirrhotic patients

Abstract: BACKGROUNDHepatic cirrhosis is associated with greater adverse event rates following surgical procedures and is thought to have a higher risk of complications with interventional procedures in general. However, these same patients often require interventional gastrointestinal procedures such as endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS). While studies examining this scenario exist, the overall body of evidence for adverse event rates associated with ERCP/EUS procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…Our study preliminarily showed that the risk of postoperative complications for patients with cirrhosis was higher than that for patients without cirrhosis. This is consistent with the results of previous studies that showed that many patients with cirrhosis require ERCP in clinical practice [1–3] . Patients with cirrhosis are considered unsuitable for ERCP because of poor hepatic synthesis often associated with platelet dysfunction and coagulopathy, which places them at a higher risk for intraoperative bleeding.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study preliminarily showed that the risk of postoperative complications for patients with cirrhosis was higher than that for patients without cirrhosis. This is consistent with the results of previous studies that showed that many patients with cirrhosis require ERCP in clinical practice [1–3] . Patients with cirrhosis are considered unsuitable for ERCP because of poor hepatic synthesis often associated with platelet dysfunction and coagulopathy, which places them at a higher risk for intraoperative bleeding.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the results of previous studies that showed that many patients with cirrhosis require ERCP in clinical practice. [1][2][3] Patients with cirrhosis are considered unsuitable for ERCP because of poor hepatic synthesis often associated with platelet dysfunction and coagulopathy, which places them at a higher risk for intraoperative bleeding. Poor coagulation during sphincterotomy can result in acute or delayed bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pooled incidence of adverse events in patients with cirrhosis was 15.5% (95% CI, 11.8%–19.2%; I 2 =96.2%). The pooled incidence of PEP reported in 21 studies 6 , 7 , 10 - 12 , 15 - 28 , 30 , 31 was 5.1% (95% CI, 3.1%–7.2%; I 2 =91.5%). The pooled incidence of ERCP-related bleeding in 24 studies 6 , 7 , 10 - 31 was 3.6% (95% CI, 2.8%–4.5%; I 2 =67.5%).…”
Section: Resultsmentioning
confidence: 98%